Beware, the snowman - Stine, R. L. (New York : Scholastic, 1997)
Jaclyn moves with her aunt to a tiny village on the edge of the Arctic Circle where every house has a snowman with a really evil smile.
RL4.
450
008-012.
3-7.
450
Accelerated Reader AR
Keywords: Snow sculpture -- Juvenile fiction; Horror stories